2021
DOI: 10.1017/s1368980021002020
|View full text |Cite
|
Sign up to set email alerts
|

Between the city and the farm: food environments in artisanal mining communities in Upper Guinea

Abstract: Objective: Artisanal and small-scale mining (ASM) is a widespread livelihood in low- and middle-income countries, however many in ASM communities face high levels of poverty and malnutrition. The food environments in ASM communities have non-agricultural rural characteristics that differ from those in urban and subsistence rural areas examined in much existing food environment literature. Design: We examine these complex external and personal food environments in ASM communities via a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 69 publications
(95 reference statements)
0
20
1
Order By: Relevance
“…We found that fresh produce of fairly high quality was available within the informal settlements, and we also found a high availability of fried foods such as french fries and mandazi (fried dough) as well as prepared meals being sold by street vendors (e.g., githeri). In contrast to other studies examining food environments in sub-Saharan Africa [18], commercially processed foods were not as prevalent in our study settings. Much of the global discussion around poor quality diets stemming from the nutrition transition has centered on an increase in ultra-processed foods.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…We found that fresh produce of fairly high quality was available within the informal settlements, and we also found a high availability of fried foods such as french fries and mandazi (fried dough) as well as prepared meals being sold by street vendors (e.g., githeri). In contrast to other studies examining food environments in sub-Saharan Africa [18], commercially processed foods were not as prevalent in our study settings. Much of the global discussion around poor quality diets stemming from the nutrition transition has centered on an increase in ultra-processed foods.…”
Section: Discussioncontrasting
confidence: 96%
“…However, much of the food environment literature has focused solely on high-income countries [14,15] and on specific dimensions (e.g., availability) of the food environment. Although there has been a growing amount of food environment research in LMICs [16][17][18][19], critical research gaps remain regarding the multitude of external food environment dimensions and individual factors that influence consumer behavior [12,[20][21][22]. These knowledge gaps limit the ability to design comprehensive interventions that have the potential to lead to marked shifts in diets and disease burdens.…”
Section: Introductionmentioning
confidence: 99%
“…We identified the projects that captured how food safety is conceptualized across different perspectives; some projects did not have information on food safety because the projects that were funded in the portfolio had different aims, not all of which covered food safety. Data from projects in the following 6 countries were included: Ghana [ 25 ], Guinea [ 26 ], India [ 27 ], Kenya [ 10 ], Tanzania [ 28 ], and Vietnam [ 29 ] ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In Guinea, Nordhagen et al [ 26 ] used stratified sampling to purposively select study sites based on their proximal distance to villages and towns. Data were collected from May 2018 to December 2019 through nonparticipant observations at mining sites ( n = 25) and markets ( n = 8), household surveys ( n = 613) and market surveys ( n = 4), and in-depth interviews with mothers ( n = 45) and food vendors ( n = 40).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation